Compromiso laboral de los empleados de la Coordinación Zonal 5- Ministerio de Inclusión Económica y Social (MIES) - Cadena Parraga, Vanessa Katiuska (2019)
The purpose of this case study is to know the causes that affect the labor commitment of the employees of the Zonal Coordination 5-Ministry of Economic and Social Inclusion (MIES) inconveniences that affect the development of labor functions among which the absenteeism, demotivation, job dissatisfaction as the most relevant aspects, which influence the daily behavior of the officials of said institution thus affecting the work performance of the staff because they do not have adequate physical space, in addition to not having the availability of Material and technological resources necessary to carry out the activities assigned in an efficient and effective way that help to carry out the administrative and social processes correctly, thus allowing to achieve results that benefit the institution, employees and the social group that depends on it